2019
DOI: 10.5121/ijwmn.2019.11102
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Performance Evaluation of Reactive, Proactive, and Hybrid Routing Protocols in Wireless Mesh Network

Abstract: This paper evaluates the energy consumption of well-known routing protocols, along with other metrics such as throughput, packet delivery ratio (PDR), and delay in different scenarios. We consider two other metrics in order to capture the efficiency of the energy consumption: e-throughput which is the ratio between the consumed energy and the throughput; and the e-PDR which is the ratio between the consumed energy and the PDR. We compare four routing protocols: AODV, OLSR, and HWMP in Reactive and Proactive mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The evaluation of reactive routing protocols [17], [66], [76], [77] showed that reactive routing introduces lower overhead as loop free since routes are only constructed when required, which is a privilege of this type of the protocol compared to proactive routing. The disadvantages of reactive routing are that, due to the initial route discovery process, there is a critical delay between the time a source node requests a route for data transmission and the time when the actual transmission takes place.…”
Section: Discussion and Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of reactive routing protocols [17], [66], [76], [77] showed that reactive routing introduces lower overhead as loop free since routes are only constructed when required, which is a privilege of this type of the protocol compared to proactive routing. The disadvantages of reactive routing are that, due to the initial route discovery process, there is a critical delay between the time a source node requests a route for data transmission and the time when the actual transmission takes place.…”
Section: Discussion and Studiesmentioning
confidence: 99%
“…Even though TORA performs well in dense networks, it does not scale by any means. Several evaluation studies showed that DSR and AODV outperform TORA [66], [67]. It was enhanced to provide better packet delivery, and acceptable routing overhead and packet latency [66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reactive, proactive, and hybrid routing protocols n wireless network have been analysed based on energy consumption during communication [4]. Performance evaluation work is carried out by considering the parameters such as throughput, delay, and packet delivery ratio.…”
Section: Related Workmentioning
confidence: 99%